Recent Understandings Toward Coronavirus Disease 2019 (COVID-19): From Bench to Bedside - Yu, Jie; Chai, Peiwei; Ge, Shengfang; Fan, Xianqun (Frontiers in Cell and Developmental Biology, 2020)
In late December 2019, an unprecedented outbreak of coronavirus disease 2019 (COVID-19) caused by SARS coronavirus 2 (SARS-CoV-2) (previously named 2019-nCoV) in Wuhan became the most challenging health emergency. Since its rapid spread in China and many other countries, the World Health Organization (WHO) declared COVID-19 a public health emergency of international concern (PHEIC) on 30th January 2020 and a pandemic on 11th March 2020. Thousands of people have died, and there are currently no vaccines or specific antiviral drugs for COVID-19. Therefore, it is critical to have a comprehensive understanding of the virus. In this review, we highlight the etiology, epidemiology, pathogenesis and pathology, clinical characteristics, diagnosis, clinical management, prognosis, infection control and prevention of COVID-19 based on recent studies.